Evaluation of the Utilization of Palm Oil Mill Liquid Waste with the Land Application method at PT. X - Izhar, Muhammad; Prayitno, Muh. Bambang; Ulqodry, T. Zia (Program Pascasarjana Universitas Sriwijaya, 2025)
Palm oil mill effluent (POME) as one of the largest wastes produced in the crude palm oil (CPO) production process is one of the significant environmental challenges in the palm oil industry. POME contains low pH and also contains organic and highly nutritious materials so that it has the potential to be utilized. The land application method has been proposed as one solution to utilize POME sustainably. This study evaluated the utilization of POME through the land application method at PT. X, with a focus on the palm oil mill liquid waste management system and its effect on surface water quality. The data obtained showed that the PT.X palm oil mill liquid waste management system already succeeded in reducing BOD levels by 64.83%. The results of surface water quality tests in the upstream and downstream water bodies around the activity location also showed that most parameters were still below the quality standards required by the government regulations. However, supervision of the implementation of land application must always be carried out because it also has a risk of water pollution if not managed properly.